The Value of Right Ventricular Longitudinal Strain in the Evaluation of Adult Patients With Repaired Tetralogy of Fallot: a New Tool for a Contemporary Challenge - Almeida-Morais, L (2018)
OBJECTIVE: The role of right ventricular longitudinal strain for assessing patients with repaired tetralogy of Fallot is not fully understood. In this study, we aimed to evaluate its relation with other structural and functional parameters in these patients. METHODS: Patients followed-up in a grown-up CHD unit, assessed by transthoracic echocardiography, cardiac MRI, and treadmill exercise testing, were retrospectively evaluated. Right ventricular size and function and pulmonary regurgitation severity were assessed by echocardiography and MRI. Right ventricular longitudinal strain was evaluated in the four-chamber view using the standard semiautomatic method. RESULTS: In total, 42 patients were included (61% male, 32±8 years). The mean right ventricular longitudinal strain was -16.2±3.7%, and the right ventricular ejection fraction, measured by MRI, was 42.9±7.2%. Longitudinal strain showed linear correlation with tricuspid annular systolic excursion (r=-0.40) and right ventricular ejection fraction (r=-0.45) (all p<0.05), which in turn showed linear correlation with right ventricular fractional area change (r=0.50), pulmonary regurgitation colour length (r=0.35), right ventricular end-systolic volume (r=-0.60), and left ventricular ejection fraction (r=0.36) (all p<0.05). Longitudinal strain (β=-0.72, 95% confidence interval -1.41, -0.15) and left ventricular ejection fraction (β=0.39, 95% confidence interval 0.11, 0.67) were independently associated with right ventricular ejection fraction. The best threshold of longitudinal strain for predicting a right ventricular ejection fraction of <40% was -17.0%. CONCLUSIONS: Right ventricular longitudinal strain is a powerful method for evaluating patients with tetralogy of Fallot. It correlated with echocardiographic right ventricular function parameters and was independently associated with right ventricular ejection fraction derived by MRI.